2019
DOI: 10.37358/rc.19.2.6962
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermal Changes in Dental Resins Enriched with Silver Nanoparticles

Abstract: Acrylic resins are frequently used in dentistry for the removable partial or complete denture but, epidemiological studies report that approximately 70% of removable denture wearers suffer from denture stomatitis. Silver nanoparticles (AgNps) incorporation aims to avoid or at least to decrease the microbial colonization over dental materials, but their influence on the mechanical features is still not very well known. A total of 100 heat curing and 100 of self-curing acrylic resin samples were made, and divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Just like in XDR, DSC curves showed that the presence of silver nanoparticles did not alter the properties of the wires. In one study, AgNPs increased thermal stability of the composites produced [25], but in a second work the incorporation of these nanoparticles in dental acrylic resins did not affect its thermal behavior [26], as well as this study. The results ensure the use of hydrothermal synthesis for the production of antimicrobial orthodontic wires.…”
Section: Discussionsupporting
confidence: 54%
“…Just like in XDR, DSC curves showed that the presence of silver nanoparticles did not alter the properties of the wires. In one study, AgNPs increased thermal stability of the composites produced [25], but in a second work the incorporation of these nanoparticles in dental acrylic resins did not affect its thermal behavior [26], as well as this study. The results ensure the use of hydrothermal synthesis for the production of antimicrobial orthodontic wires.…”
Section: Discussionsupporting
confidence: 54%
“…Inappropriate care and maintenance of CDs contribute to low patient satisfaction 2 . In addition, inadequate CD hygiene can lead to oral infections because the micro‐porous acrylic surfaces of CDs increase the risk of colonization of Candida albicans and bacteria 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…can lead to oral infections because the micro-porous acrylic surfaces of CDs increase the risk of colonization of Candida albicans and bacteria. 3,4 The objective of denture care and maintenance is to eliminate the plaque biofilm adhering to denture surface, hence preventing the initiation of oral disease. 1 Improper CD care and maintenance can cause oral lesions such as, commissural cheilitis, inflammatory papillary hyperplasia, burning mouth syndrome, mouth ulcers and flappy ridge.…”
mentioning
confidence: 99%
“…Acrylic dental resins, especially poly-methyl-methacrylate (PMMA) resin, are commonly used in dentistry as denture base materials due to their advantages, including their relatively high strength, acceptable hardness, color stability, insolubility in the oral cavity, low weight, and low conductivity [ 1 , 2 ]. However, these materials have numerous drawbacks which are frequently reported by practitioners, the most common of which are poor mechanical strength, susceptibility to staining [ 3 ], curing shrinkage, and water sorption [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%